2022
DOI: 10.3390/bios12020078
|View full text |Cite
|
Sign up to set email alerts
|

A Sensitive Monoclonal-Antibody-Based ELISA for Forchlorfenuron Residue Analysis in Food Samples

Abstract: In this study, forchlorfenuron (CPPU) was coupled with succinic anhydride to yield a CPPU hapten (CPPU-COOH), and a high-affinity monoclonal antibody (mAb) that can specifically recognize CPPU was produced. Using this mAb as a recognition reagent, a sensitive indirect competitive enzyme-linked immunosorbent assay (icELISA) for CPPU was optimized, which exhibits an IC50 of 1.04 ng/mL, a limit of detection of 0.16 ng/mL, and a linear range of 0.31–3.43 ng/mL for CPPU. Cross-reactivity percentages with six analog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 46 publications
0
6
1
Order By: Relevance
“…As listed in Table 1 , anti-CPPU mAb 14G1 showed extremely inconspicuous CRs with analogues in the MB-based assay and icELISA systems. When compared with previous studies [ 14 , 16 ], the ELISA-based antibodies exhibited obvious cross-reaction with thidiazuron. However, in the present study, an MB-based assay and icELISA-based mAb 14G1 had negligible cross-reaction with thidiazuron and other listed compounds, which exhibited better selectivity and could effectively guarantee the specific detection of CPPU.…”
Section: Resultsmentioning
confidence: 65%
See 3 more Smart Citations
“…As listed in Table 1 , anti-CPPU mAb 14G1 showed extremely inconspicuous CRs with analogues in the MB-based assay and icELISA systems. When compared with previous studies [ 14 , 16 ], the ELISA-based antibodies exhibited obvious cross-reaction with thidiazuron. However, in the present study, an MB-based assay and icELISA-based mAb 14G1 had negligible cross-reaction with thidiazuron and other listed compounds, which exhibited better selectivity and could effectively guarantee the specific detection of CPPU.…”
Section: Resultsmentioning
confidence: 65%
“…Additionally, we have provided a detailed comparison of the analytical performance of these two developed methods with those of the previously documented immunoassay methods for CPPU detection, as shown in Table S2 . The comparison results showed that the total analysis time of the developed MB-based assay was much less than other microplate-based enzyme immunoassays for CPPU [ 13 , 14 , 15 , 16 ], and they were even comparable to strip-based immunochromatography, which can complete the assay in 30 min [ 15 ]. Moreover, the IC 50 and LOD values of the MB-based assay for CPPU were far lower than the reported immunoassays.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, various analysis methods of CPPU have been reported, such as high-performance liquid chromatography (HPLC) [7], surfaceenhanced Raman spectroscopy (SERS) [8], enzyme-linked immunosorbent assay (ELISA) [9], and electrochemistry (EC) [10]. These methods not only have the advantages of high sensitivity and specificity, but also have disadvantages such as long time, complex operation and high costs [11].…”
Section: Introductionmentioning
confidence: 99%